2019
DOI: 10.21273/hortsci14377-19
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity and Polyphenolic Compounds of Blackberries Produced in Different Climates

Abstract: Antioxidants are compounds with varied chemical structures that are affected by biotic and abiotic factors. The objective of this study was to characterize and compare bioactive compounds and the antioxidant capacity of fruit from four blackberry cultivars produced under different climatic conditions. Ascorbic acid content, total polyphenols, flavonoids, monomeric anthocyanins and antioxidant activity of the fruit were evaluated, and high levels of bioactive compounds as well as antioxidant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Whereas, other researchers found that the blackberries have greater concentration of total phenolic compound than strawberries and raspberries, which are grown in tropical conditions [ 99 ]. Croge, et al [ 100 ] found fruits grown in temperate region have higher polyphenol content.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas, other researchers found that the blackberries have greater concentration of total phenolic compound than strawberries and raspberries, which are grown in tropical conditions [ 99 ]. Croge, et al [ 100 ] found fruits grown in temperate region have higher polyphenol content.…”
Section: Resultsmentioning
confidence: 99%
“…Consumers want blackberries with extremely dark purple fruits and a shiny appearance, since a dull colour can give the fruit the appearance of either freshness or excessive fruit age [ 21 , 22 ]. The colour of blackberries depends on various factors, such as genotype, production conditions, fruit ripening stage, harvesting time, climate and soil, as well as storage conditions [ 23 , 24 ]. The measured colour parameter h ° in blackberries ranged between 346 and 351, which means a dark purple colour, while the L* value was from 19.8 to 23.9, which gives the fruit an extremely dark, almost black colour ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The content of vitamin C in fruits is certainly genetically determined, so there are big differences among individual genotypes. An approximately two times higher vitamin C content has been reported in wild blackberries, i.e., from 20.4 to 28.1 mg/100g [ 23 ]. Similar values of vitamin C to our results have been reported in the cultivars ‘Jumbo’, ‘Blacksatin’ and ‘Dirksen’ (7.1 to 9.6 mg/100 g) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Secondary plant metabolites such as flavonoids and phenolic acids play significant roles in plant defense mechanisms against plagues of insects and microorganisms, as well as in front of climatic or farming factors; hence, it is not surprising that their levels depend on the stress suffered by the plants. More recent specific examples to illustrate this dependence deal with the study of the antioxidant features and phenolic contents of blackberry extracts cultivated in different climates [37], anthocyanin levels of blueberry species as a function of ripening or altitude [38], essential oil, carotenoid, polyphenol composition of Thymus sp. under controlled growing conditions (e.g., temperature and humidity) [39], the compositional profiles of essential oils and polyphenols of various medicinal extracts of plants grown in different altitudes [40], as well as seasonal variations on bioactive compounds [41].…”
Section: Introductionmentioning
confidence: 99%